2013
DOI: 10.2340/16501977-1207
|View full text |Cite
|
Sign up to set email alerts
|

Secondary health conditions in persons with spinal cord injury: A longitudinal study from one to five years post-discharge

Abstract: Secondary health conditions are common in the first years post-discharge following spinal cord injury, and their course seems to be relatively stable. These results emphasize the number of health issues that must be considered during post-injury care of persons with spinal cord injury living in the community, and the importance of a well-coordinated interdisciplinary approach from specialized rehabilitation centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
112
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 31 publications
13
112
0
Order By: Relevance
“…4,5 In a sample of SCI survivors, the prevalence of problematic spasticity at 1, 3 and 5 years following SCI was 35%, 31% and 27%, respectively. 5 These findings agree with the observations of Levi et al 6 and Sköld et al 3 Adriaansen et al 7 reported problematic spasticity in 28-34% of individuals with SCI 1-5 years after discharge from inpatient rehabilitation. However, these studies do not describe how hindrance due to spasticity develops in the early phase after SCI.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…4,5 In a sample of SCI survivors, the prevalence of problematic spasticity at 1, 3 and 5 years following SCI was 35%, 31% and 27%, respectively. 5 These findings agree with the observations of Levi et al 6 and Sköld et al 3 Adriaansen et al 7 reported problematic spasticity in 28-34% of individuals with SCI 1-5 years after discharge from inpatient rehabilitation. However, these studies do not describe how hindrance due to spasticity develops in the early phase after SCI.…”
Section: Introductionsupporting
confidence: 80%
“…The percentages of individuals who experienced a lot of hindrance during activities of daily living were relatively low. In other studies 3,[5][6][7] hindrance due to spasticity in general was measured. Our study gives more detailed information about the occurrence of hindrance due to spasticity in daily living and goals for therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have investigated QOL and incidence or prevalence of complications after SCI in high income countries. [1][2][3] Some studies have also examined these issues in LMICs. [4][5][6][7] However, few studies sample in a representative way-most, instead, rely on samples of convenience.…”
Section: Introductionmentioning
confidence: 99%